Caracterização perceptiva do campus da Universidade Federal de Sergipe “Prof. José Aloísio de Campos” por diferentes grupos socioculturais de interação - Randow, Priscila Christina Borges Dias (2011)
This research aims to characterize the campus of the Universidade Federal de Sergipe Prof. José Aloisio de Campos , from the perception of different groups socio-cultural interaction (undergraduates and graduate students, staff, teachers, people from the surroundings and managers). The methodology used to investigate the perception system is based on the model of Whyte (1977), which describes the state variables (characteristics and experience of individuals and groups), the output variables (choice of uses) and the processes of perception (perception of meaning, identity and structure). The research was qualitative with data collected by questionnaires and by standardized interview, associated with the chart test of mental map. In various aspects investigated were no differences in the perceptions of individuals and groups, found in the formation of perceptual images, maps and summaries for the different distinct patterns of interaction, system utilization, value systems and socioeconomic and cultural. The conjunction of the different aspects analyzed shows that all groups interact more strongly perceive the built-up areas than the areas of natural study system. The groups also have a great bond with the campus Prof. José Aloísio de Campos and its surroundings, resulting in the perception of impacts and the subsequent choice of care for the system, such as structuring the physical space and the conservation and preservation of natural areas, associated with the main activities of study and work. The results confirm the importance of the study of environmental perception on project design management and planning of the university area, respecting the views of groups working in this space. To advance an environment at the Universidade Federal de Sergipe , with the balance between the current and future growth and conservation of the natural environment, makes it necessary to investigate the system of environmental perception of the other campuses and continuous monitoring of the campus under study, since the maps and perceptive images of interacting groups were prepared in the present tense.